Effect of calcination temperature on visible near-infrared reflectance of aluminum-doped chromium. (January 2020) - Zhang, Linbo; Wu, Pan; Chen, Hui; Yuan, Le; Yang, Guang; Xie, Haiyan; Liang, Difei; Xie, Jianliang; Deng, Longjiang
Abstract: The present study reports the preparation and characterization of Cr2 O3 –Al2 O3 composite pigments with low visible and high near-infrared (NIR) reflectance. The complex pigments were prepared by Solid-State Reaction Sintering Method. The effects of calcination temperature and Al2 O3 content on reflectance were investigated by SEM, X-ray diffraction, XPS and UV-VIS-NIR spectroscopy. And the resistance of the complex Cr2 O3 –Al2 O3 pigments were further discussed to analyze the carrier concentration. The results reveal that the complex Cr2 O3 –Al2 O3 pigments having good optical performance and acid-alkali resistance can be prepared by the calcination of the precursor at about 1000 °C. The prepared complex Cr2 O3 –Al2 O3 pigments will be beneficial in applications such as cool materials used for buildings with energy saving performance.